Measurement Of Total Productive Maintenance (TPM) Using The Overall Equipment Effectiveness (OEE) Method On Fermentation Machinery At Pt. Indo Acidatama TbkMeasurement Of Total Productive Maintenance (TPM) Using The Overall Equipment Effectiveness (OEE) Method On Fermentation Machinery At Pt. Indo Acidatama Tbk - Muhammad Firnas Balisca Putra; Roni Zakaria (Fakultas Teknik Universitas Wahid Hasyim, 2023)
Ethanol, or ethyl alcohol, has many applications in a variety of industries, including as a solvent, fuel, and in pharmaceuticals. Demand for ethanol in Indonesia is high, but domestic production is not sufficient, which prompted the establishment of PT. Indo Acidatama Tbk in 1986. This company produces ethanol from sugar cane molasses through a fermentation process using the yeast saccharomyces cerevisae strain Kyowa. The fermentation process requires good care to ensure optimal results and prevent machine failure. This research aims to measure the Overall Equipment Effectiveness (OEE) value of the fermentation machine at PT Indo Acidatama, identify the factors that influence the production performance of the fermentation machine, and determine the main causes of losses that affect the effectiveness of the fermentation machine. The research results show that the OEE value of the fermentation machine at PT Indo Acidatama in January 2023 is 85%, which is in accordance with JIP standards. The main causes of loss of machine effectiveness are breakdown losses (8.7%), reduced speed losses (5.9%), and rework losses (0.2%). To increase the effectiveness of fermentation machines, it is recommended to adjust process parameters, provide training to staff, and carry out regular data monitoring.